Peran PPAH Tani Makmur dalam Pemberdayaan Petani Cabai Rawit di Desa Kedungasri Kecamatan Tegaldlimo Kabupaten Banyuwangi - Firda Sholihatun Nisa; Rokhani Rokhani; Sudarko Sudarko; Nurul Dwi Novikarumsari (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine research on the application of social media in agricultural extension activities by analyzing research themes/topics, research methods, and research results. The research method uses qualitative descriptive by processing data including data reduction, data presentation and conclusions. The results showed that the role of PPAH Tani Makmur only played a role in three 3 tasks, namely tasks in the organization, resource tasks and service tasks. Tasks in the organization focus on planning to achieve a goal and mediating between farmers and agricultural extension workers in conveying aspirations and needs in farming. The resource task focuses on mobilizing or directing local resources to solve problems experienced by farmers through training activities. The task of service focuses on servicing the means of production and access to capital without going through difficult bureaucracy).